Sealing adhesive and lid for optical element packages
A sealing bonding material using solder powder, silver nanoparticles, and metallic selenium forms a stable, UV-resistant hermetic seal for UV-LEDs and laser light sources, addressing hermetic sealing challenges with UV-LEDs and laser light sources.
Patent Information
- Application Number
- JP2020188426
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-11-12
AI Technical Summary
Existing sealing materials for UV-LEDs and short-wavelength laser light sources face issues with hermetic sealing due to stress from high temperatures, material instability, and environmental limitations, leading to potential short circuits and unreliable performance.
A sealing bonding material composed of solder powder, silver nanoparticles coated with a coating material, metallic selenium, and a solvent, along with oxidation film inhibitors and removers, allows for airtight sealing under mild conditions, using components like Sn-Bi solder and silver nanoparticles to form a bonding layer.
The material provides a stable, UV-resistant hermetic seal that withstands short wavelength light emissions, ensuring long-term reliability and airtightness without damage, suitable for UV-LEDs and laser light sources.
Smart Images

Figure 0007608791000002 
Figure 0007608791000003 
Figure 0007608791000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealing adhesive material used to seal optical elements that require airtight sealing, such as UV-LEDs and short-wavelength, high-output laser light sources, and a lid for optical element packages in which a bonding layer made of the adhesive material is pre-formed on a window material. [Background technology]
[0002] In recent years, elements capable of emitting light in the deep ultraviolet region have been attracting attention for applications such as inactivating coronaviruses and sterilizing water. Among these, ultraviolet light-emitting diodes (UV-LEDs) have been attracting attention as devices with low environmental impact. Elements that emit deep ultraviolet light are expected to be used in harsh environments, such as places with high humidity, depending on the environment in which they are used. In such cases, for example, if moisture comes into contact with the electrical circuit part where the LED element is located, it is thought that this could cause problems such as short circuits. For this reason, one of the performance requirements for the package is that it is hermetically sealed.
[0003] Currently, when UV-LED elements are encapsulated in a normal resin mold, the resin deteriorates due to the short-wavelength light emitted by the element, so a surface-mount package (hereinafter referred to as SMD PKG) that uses a lid with a synthetic quartz window material, for example, is the most commonly selected package for optical elements.
[0004] When hermetically sealing an SMD PKG, a metal adhesive is used as a sealant between the lid and the container member, and a method has been proposed in which gold-tin solder, which has a proven track record in SAW devices, is used as the sealant (Patent Document 1: International Publication No. 2016-103547). In addition, when using an adhesive containing a metal component such as solder, the oxide film formed by the metal reduces wettability, so a method has been proposed in which a metal adhesive layer is formed from the metal of the solder material while reflowing with formic acid to remove the oxide film (Patent Document 2: JP Patent Publication No. 2016-078095). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2016 / 103547 [Patent Document 2] JP 2016-078095 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the gold-tin solder described in Patent Document 1 generates a large stress during the cooling process after it is melted by applying heat to form a bond, so the sealability of the bond is easily compromised and there is a risk to the stable supply of materials due to fluctuations in the price of gold. On the other hand, the method using formic acid described in Patent Document 2 is difficult to handle because the working environment is limited, and it is difficult to say it is a general method.
[0007] The present invention has been made in consideration of the above circumstances, and aims to provide a simple and safe sealing adhesive that is primarily composed of a metal-based material capable of creating an airtight seal, can be used stably for long periods of time without being affected by heat or short-wavelength light when sealing elements such as modern UV-LEDs and short-wavelength, high-output laser light sources, and can perform bonding under gentle bonding conditions, and a lid for optical element packages on which a bonding layer made of the adhesive is formed. [Means for solving the problem]
[0008] As a result of extensive research into achieving the above-mentioned object, the inventors have discovered that a composition that essentially contains solder powder, silver nanoparticles coated with a coating material, and a solvent as a sealing material for a package that can achieve an airtight seal, and further contains metallic selenium or an agent for preventing or removing an oxide film, can be used stably for a long period of time, and can form a bonding layer under mild bonding conditions, which has led to the creation of the present invention.
[0009] Accordingly, the present invention provides the following sealing adhesive material and lid for an optical element package. 1. Solder powder, silver nanoparticles coated with a coating material, Metallic selenium, and The solvent Contains and the content of said metallic selenium but 0.5~5% by mass is A sealing bonding material characterized by the above. 2. The sealing bonding material according to 1, characterized in that the solder powder contains tin. 3. Previous Deposit 3. The sealing bonding material according to claim 1 or 2, wherein the melting point of the solder powder is lower than the melting point of metal selenium. 4. The sealing bonding material according to 2 or 3, characterized in that the solder powder contains tin and further contains bismuth. 5. The sealing bonding material according to 4, wherein the solder powder further contains one or more elements selected from the group consisting of zinc, indium and silver. 6. The sealing bonding material according to any one of 1 to 5, wherein the coating material is selected from the group consisting of aliphatic carboxylic acids, higher alcohols, and amines. 7. The sealing bonding material according to any one of 1 to 6, wherein the average primary particle diameter of the silver core portion of the silver nanoparticles is 20 to 90 nm, as measured by the following method. Measurement method: The average primary particle size was calculated as the arithmetic mean value of 20 randomly selected silver core particles observed with a scanning electron microscope (SEM). 8. A sealing bonding material according to any one of 1 to 7, characterized in that the solvent contains one or more compounds selected from the group consisting of terpenes, monoterpene alcohols, alkyl alcohols, and naphthenic hydrocarbons. 9. The median diameter D of the metallic selenium by dynamic light scattering method 50 9. The sealing bonding material according to any one of 1 to 8, comprising metallic selenium having a size (volume basis) of 5 to 20 μm. 10. A sealing bonding material according to any one of 1 to 9, characterized in that it contains one or more oxide film removers selected from the group consisting of aliphatic carboxylic acids and polycarboxylic acids. 11. 11. The sealing bonding material according to any one of 1 to 10, which contains one or more antioxidants selected from the group consisting of hindered phenols, hindered amines, hydroquinones, and phenothiazines. 12. A lid for an optical element package comprising a window material provided in front of a housing member in which an optical element is housed, in the direction of light emission of the optical element, and a metal-based bonding layer formed at a portion where the window material contacts the housing member, wherein the sealing bonding material described in any one of 1 to 11 is applied in a frame shape to the window material to form the metal-based bonding layer. 13. 13. The lid for an optical element package according to claim 12, wherein the window material is synthetic quartz glass. 14. A lid for an optical element package as described in 12 or 13, characterized in that the metal-based bonding layer formed from the sealing bonding material as described in any one of 1 to 11 is in a semi-cured state (B-Stage). Effect of the Invention
[0010] According to the present invention, it is possible to provide a sealing bonding material that can easily form under mild conditions a metal bonding layer having good airtight sealing properties and UV resistance, which are required when sealing elements that emit short-wavelength light such as UV-LEDs, and that can be used stably for a long period of time. [Brief description of the drawings]
[0011] [Figure 1] 1A shows an example of a lid for an optical element package of the present invention, in which (A) is a plan view, (B) is a cross-sectional view taken along line BB in (A), and (C) is a schematic cross-sectional view showing an example of an optical element package in which an accommodating member is closed with the lid. [Diagram 2] 2 is a graph showing the results of TG-DTA measurement of the sealing bonding material of Example 1. [Diagram 3] 1 is a graph showing the results of TG-DTA measurement of the sealing bonding material of Example 2. [Figure 4] 1 is a graph showing the results of TG-DTA measurement of the sealing bonding material of Example 3. [Diagram 5] 1 is a graph showing the results of TG-DTA measurement of the sealing bonding material of Example 4. [Figure 6] 1 is a graph showing the results of TG-DTA measurement of the sealing bonding material of Comparative Example 1. [Figure 7] 1 is a graph showing TG curves obtained by TG-DTA measurement of the sealing bonding materials of Examples 1 and 2 and Comparative Example 1, in which the vertical axis represents the weight change (%) and the horizontal axis represents the temperature (° C.). [Figure 8] 1 is a backscattered electron image photograph taken by a scanning electron microscope (SEM) showing a cross section of a film made of the sealing bonding material of Example 2. [Figure 9] 1 is a backscattered electron image photograph taken by a scanning electron microscope (SEM) showing a cross section of a film made of a sealing bonding material of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below. The sealing adhesive of the present invention essentially contains solder powder, silver nanoparticles coated with a coating material, and a solvent, and further contains at least one selected from metallic selenium, an oxidation film inhibitor, and an oxidation film remover. The sealing adhesive can be applied in a frame shape to a window material 1 made of a transparent substrate that can transmit light to form an adhesive layer 2, as shown in Figure 1, to form a lid for an optical element package, and can be suitably used as a sealing material for optical element packages that require airtightness, such as UV-LEDs.
[0013] [Solder powder] 1(B), in order to obtain airtightness, it is essential that the bonding layer 2 be densified. In addition, since the optical element 4 has poor heat resistance, the solder material used in the present invention is required to melt at a low temperature to form the bonding layer 4.
[0014] From the above viewpoint, in the process of joining the window material 1 to be joined by the sealing bonding material and the housing member 3 on which the optical element 4 is arranged, the melting point of the solder powder is preferably low in order to complete the joining at a low temperature (for example, 150 to 250°C), and when the sealing bonding material of the present invention contains the above-mentioned metallic selenium, the melting point of the solder powder is preferably lower than the melting point of the metallic selenium (221°C). Specifically, the melting point is preferably 200°C or lower, more preferably 180°C or lower, and even more preferably 160°C or lower. The lower limit of the melting point of the solder powder is usually 100°C or higher. In order to achieve the above temperature range, although there is no particular limitation, it is preferable that the solder contains Sn as a component.
[0015] Furthermore, even if a window material exhibits transparency and high transmittance characteristics in the initial state, for short wavelengths such as those in the ultraviolet region, if the window material contains metal or resin components, deterioration will occur from these parts and long-term reliability will not be obtained, so synthetic quartz is generally preferably selected as the window material 1. When using synthetic quartz as the window material 1, in order to obtain reliable adhesion to it, it is more preferable that the solder components contain Bi, which can be fixed to the synthetic quartz by an anchor effect.
[0016] Such solder powder is not particularly limited, but is preferably one or more selected from the group consisting of Sn-Bi solder, Sn-Zn-Bi solder, and Sn-In-Ag-Bi solder. More specifically, examples include Sn42.0-Bi58.0, Sn88.0-In8.0-Ag3.5-Bi0.5 (manufactured by Mitsui Mining & Smelting Co., Ltd.), and Sn89.0-Zn8.0-Bi3.0 (manufactured by Sasaki Handa Kogyo Co., Ltd.).
[0017] D of the primary particles of solder particles 50Considering that the bonding material is applied by screen printing, the volume average median 50% diameter is preferably 1 to 30 μm, more preferably 1 to 20 μm, from the viewpoint of passing through the mesh of a screen mask. If the particle diameter is too small, the specific surface area of the oxide film formed by the metal in the solder component becomes large, which may cause a problem that the antioxidant is not sufficiently effective even if it is added. The median diameter is measured by dynamic light scattering.
[0018] The content of the solder powder is not particularly limited, but is preferably 30 mass % or more, more preferably 45 mass % or more, and preferably 80 mass % or less, more preferably 70 mass % or less of the sealing bonding material.
[0019] [Silver nanoparticles coated with a coating material] The metal nanoparticles contained in the sealing adhesive material of the present invention are very fine particles, so they need to be coated with an appropriate substance to prevent spontaneous sintering caused by interaction between primary particles. From this viewpoint, the metal nanoparticles are used in a state where the surfaces are coated with a coating material (for example, a state where a thin layer of a liquid or solid substance is attached to the surface) before the adhesive layer is formed.
[0020] In the present invention, silver nanoparticles are used in which the metal constituting the metal nanoparticles is silver, an alloy containing silver, or a mixture of silver and other metals, but preferably those consisting essentially of silver are used. When the silver nanoparticles are an alloy or a mixture, it is preferable that silver accounts for 80 mass% or more of the total metal nanoparticles from the viewpoint of the stability of the sintered body formed by the silver nanoparticles.
[0021] The coating material for the core particles of the silver nanoparticles (hereinafter referred to as "silver core particles") may be a known organic material that can be attached to general metal nanoparticles. Examples of the organic material include organic polymers such as aliphatic carboxylic acids, higher alcohols, and amines, and organic molecules.
[0022] The coating material is preferably one that is temperature responsive and separates from the silver core particles. The coating material is detached from the silver core particles by increasing the temperature, thereby obtaining a sintered body with high bonding strength. The temperature at which the coating material separates from the silver core particles (separation temperature) is preferably a temperature equal to or higher than the sintering temperature of the coated silver particles, more preferably a temperature 10°C higher than the sintering temperature of the coated silver particles, so that the silver core particles, which are nanoparticles, can be sintered quickly when the coating material is detached from the silver core particles. On the other hand, the separation temperature of the coating material is preferably a temperature 50°C higher than the sintering temperature of the coated silver particles or lower [(sintering temperature of the coated silver particles + 50°C) or lower]. Here, the temperature at which the coating material separates from the coated silver particles (separation temperature) can be the temperature at which the coated silver particles start to neck together. Necking refers to the bonding of the silver core particles together due to the separation of the coating material from the surface of the silver core particles. The temperature at which necking begins can be confirmed by measuring the weight change that accompanies the loss of coating material from the surface of the silver core particles during necking (TG-DTA measurement, thermogravimetry, differential thermal analysis), and the temperature at which the weight change occurs in the TG curve obtained from the TG-DTA measurement can be regarded as the separation temperature.
[0023] As the coating material for coating the silver core particles, organic polymers and organic molecules such as aliphatic carboxylic acids, higher alcohols, and amines can be used as described above, but aliphatic carboxylic acids are particularly preferred. Aliphatic carboxylic acids are compounds having one or more carboxyl groups in an aliphatic compound, and the carboxyl groups are usually adsorbed and arranged on the surface of the silver core particles. From the above viewpoint, a structure in which one carboxyl group is substituted on an aliphatic compound, that is, a compound having an aliphatic hydrocarbon group and one carboxyl group, is preferred.
[0024] The aliphatic hydrocarbon group constituting the aliphatic carboxylic acid is preferably a straight-chain aliphatic hydrocarbon group, from the viewpoint of facilitating smooth detachment of the coating material in response to temperature by forming a monomolecular film, such as an LB film (Langmuir-Blodgett film), at a certain density on the surface of the silver core particle.
[0025] In the aliphatic carboxylic acid, the number of carbon atoms in the aliphatic group is preferably 5 or more, and more preferably 7 or more, in consideration of the hydrophobic interaction, dispersibility, and oxidation resistance of the coating material molecules. On the other hand, in consideration of steric hindrance when the coating material molecules are adsorbed to the silver core particles, the number of carbon atoms is preferably 16 or less, and more preferably 13 or less. Specific examples include octanoic acid, undecanoic acid, and dodecanoic acid. The aliphatic carboxylic acid may be used alone or in combination of two or more kinds of substances.
[0026] The average primary particle diameter of the coated silver nanoparticles is preferably 1 to 500 nm, more preferably 10 to 400 nm, and further preferably 20 to 300 nm. If the average primary particle diameter is within such a range, the absolute number of coating material molecules attached to the particles increases, which increases the hydrophobic interaction of the coating material molecules, thereby reducing the possibility of a problem in which smooth detachment is difficult to occur. The average primary particle diameter of the coated silver nanoparticles is calculated as the arithmetic average value of any 20 coated silver nanoparticles observed with a scanning electron microscope (SEM). In addition, from the viewpoint that the temperature at which the coating material is detached is easily controlled if the particle diameter is as uniform as possible, the polydispersity of the particle size distribution of the coated silver nanoparticles is preferably in the range of 1.00 to 1.10.
[0027] The content of the coated silver nanoparticles is not particularly limited, but is preferably 20% by mass or more, more preferably 25% by mass or more, and preferably 70% by mass or less, more preferably 50% by mass or less of the sealing bonding material.
[0028] [Silver core particles] The average primary particle diameter of the silver core particles without a coating material is not particularly limited and can be appropriately selected from the viewpoint of the sintering temperature, etc. Specifically, the average primary particle diameter of the silver core particles can be appropriately selected in the range of 90 nm or less, and from the viewpoint of low-temperature sintering, it is more preferable if it is 80 nm or less. In addition, the average primary particle diameter of the silver core particles is usually 1 nm or more, but from the viewpoint of the cost of producing silver nanoparticles, it is more preferable if it is 20 nm or more. The average primary particle diameter of the silver core particles is calculated as the arithmetic average value of any 20 silver core particles observed with a scanning electron microscope (SEM).
[0029] The shape of the silver core particles is not particularly limited, but it is preferable that the silver core particles have a spherical shape, which is a three-dimensional structure from which the coating material can be easily removed.
[0030] [solvent] The solvent in the sealing bonding material of the present invention can be appropriately selected from solvents capable of dispersing the solder powder and the coated silver nanoparticles, as well as metal selenium, an oxide film inhibitor, and an oxide film remover, which will be described later. For example, a solvent containing one or more compounds selected from terpenes, monoterpene alcohols, alkyl alcohols, naphthenic hydrocarbons, etc. can be used. Among them, although not particularly limited, from the viewpoint of chemical stability and dispersibility of the substances contained in the sealing bonding material, a solvent containing one or more selected from the group consisting of an aliphatic amine solvent, an aliphatic alcohol solvent, a terpine acetate solvent, an aliphatic alkane solvent, and a carbitol solvent is preferable. The solvent may be used alone or in combination of two or more to form a mixed solvent.
[0031] Specific examples of the aliphatic amine solvent include octylamine, dodecylamine, and oleylamine. Specific examples of the aliphatic alcohol solvent include hexanol, octanol, decanol, and dodecanol. Specific examples of the terpine acetate solvent include 1,8-terpine-1-acetate, 1,8-terpine-8-acetate, and 1,8-terpine-1,8-diacetate. Specific examples of the aliphatic alkane solvent include octane, decane, and dodecane. Specific examples of the carbitol solvent include butyl carbitol and hexyl carbitol.
[0032] When the sealing adhesive material is applied by screen printing, the solvent preferably contains a terpine acetate-based solvent, taking into consideration compatibility with the emulsion of the screen mask and the precision of the pattern. As the terpine acetate-based solvent, for example, Tersolv THA-90 and Tersolv THA-70 manufactured by Nippon Terpene Chemical Co., Ltd. can be used.
[0033] The content of the solvent is preferably 1 to 30 mass %, more preferably 5 to 20 mass %, based on the total amount of the composition contained in the sealing bonding material of the present invention. If the content of the solvent is within this range, it is possible to reduce the possibility of a defect that the viscosity is not appropriate for screen printing and the accuracy of the printed pattern is not easily obtained.
[0034] [Metallic selenium] When a sealing material using a metal-based material is bonded under heat and pressure in the atmosphere, oxygen in the air reacts with the constituent metal species by heat energy to form oxides, forming an oxide film on the surface. It is believed that this oxide film inhibits the wettability of the bonding material components and is one of the factors that hinders the densification of the bonding layer. Therefore, the sealing bonding material of the present invention contains a substance that inhibits the reaction of oxygen with the metal that constitutes the sealing bonding material, thereby suppressing the formation of an oxide film.
[0035] Selenium is a group 16 element, and has properties similar to those of oxygen when considering the electron shells and electron orbitals of the atom. Therefore, instead of oxygen bonding with silver to form silver oxide, selenium can bond with silver to form a compound such as silver selenide. Selenium inhibits the bonding of metals with oxygen, which means that it has an antioxidant effect.
[0036] From the viewpoint of performing bonding under mild bonding conditions, it is preferable that the sealing bonding material of the present invention can be bonded well under relatively low temperature conditions of, for example, 250°C or less, but it is expected that selenium, which has a bulk melting point of 221°C, will melt during the bonding process and form an alloy with other metals. In addition, it is expected that the remelting point will be increased by alloying, and it is believed that there will be no problem with heat resistance.
[0037] When metallic selenium is added as an antioxidant to the sealing bonding material of the present invention, the amount of selenium added is not particularly limited from the viewpoint of obtaining a necessary and sufficient antioxidant effect and from the viewpoint of suppressing the problem of not being able to absorb all the selenium when other metal species react with selenium to form an alloy, but is preferably 0.5 to 5 mass%, more preferably 1 to 3 mass%. In addition, the median diameter D of the metallic selenium added, as measured by dynamic light scattering, is 50 Considering the opening diameter of the mesh of a screen mask when using screen printing, the volumetric size is preferably 5 to 20 μm, and more preferably 5 to 10 μm. As the metallic selenium, for example, SEE01PB (Kojundo Chemical Laboratory Co., Ltd.) can be used.
[0038] [Anti-oxidation agent] As a method for preventing the oxidation of metal species that are components of the sealing bonding material of the present invention, a method for preventing the formation of an oxide film using an organic substance is also effective. In this case, the oxidation film inhibitor can preferably contain one or more types of oxidation film inhibitors selected from the group consisting of hindered phenols, hindered amines, hydroquinones, and phenothiazines. In addition, additives used in the sealing bonding material of the present invention, including this oxidation film inhibitor, can be appropriately selected from those that are soluble or dispersible in the above-mentioned solvent. However, those that contain sulfur in their structure are not actively selected because they induce sulfurization of silver.
[0039] Examples of the hindered phenols include Irganox 1010, Irganox 1076, Irganox 1135 (BASF Ltd.), Adeka STAB AO series (ADEKA Corporation), etc. Examples of the hindered amines include HALS-based ones, such as TMPS-E (Shin-Etsu Chemical Co., Ltd.), Adeka STAB LA series (ADEKA Corporation), etc. Examples of the hydroquinones include hydroquinone, 4-methoxyphenol (MEHQ), etc.
[0040] When an antioxidant is added to the sealing bonding material of the present invention, the amount of the antioxidant is preferably 0.5 to 10 mass %, and more preferably 1 to 5 mass %, from the viewpoint of obtaining a sufficient antioxidant effect and preventing organic matter from remaining in the bonding layer after bonding and causing deterioration when irradiated with UV light.
[0041] [Oxide film remover] The sealing bonding material of the present invention is assumed to be used for bonding in an atmospheric environment. That is, it is used in an environment where an infinite amount of oxygen is supplied. That is, it is suggested that oxidation of the metal species that are the components of the sealing bonding material may be unavoidable. For this reason, in order to improve the wettability of the components during bonding, which is necessary for a bonding material to have airtight sealing properties, it is preferable to contain an oxide film remover that removes the oxide film that inhibits wettability.
[0042] As an oxide film remover for removing the oxide film of the metal species that is a component of the sealing bonding material of the present invention, an acidic substance having a carboxyl group in its structure, such as an aliphatic carboxylic acid or a polycarboxylic acid, is preferable. In order to smoothly cause the chemical reaction for removing the oxide film, the carboxyl group is preferably located at the end of the main chain.
[0043] Specific examples of oxide film removers include acetic acid, propionic acid, caproic acid, capric acid, lauric acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, glutamic acid, aspartic acid, lauroyl sarcosine, cocoyl sarcosine, and oleoyl sarcosine.
[0044] When an antioxidant is added to the sealing bonding material of the present invention, the amount added is preferably 0.5 to 10 mass %, and more preferably 1 to 5 mass %, from the viewpoint of obtaining a sufficient oxide film removal effect and preventing a decrease in bonding strength due to improved wettability of the metal after bonding.
[0045] [Lid for optical element packages] The sealing adhesive material of the present invention can be applied to a portion of a transparent substrate that is to serve as a window material and is capable of transmitting light, the portion being in contact with a container member, to form a lid for an optical element package.
[0046] The lid for optical element package is, for example, as shown in the cross-sectional view and the plan view in Fig. 1 (A) to (C), a bonding layer 2 is formed on the surface of a window material 1, for example, on the outer peripheral edge of the main surface of the window material 1, which is the portion where the window material 1 contacts the housing member 3 for housing an optical element 4. The bonding layer 2 may be formed on the side surface in addition to the main surface of the window material 1, but is preferably formed only on the main surface, in particular, only on one main surface that contacts the housing member 3 in which the optical element 4 is housed. As shown in Figs. 1 (A) and (B), the bonding layer 2 is preferably formed on the outer peripheral edge of the main surface of the window material 1 so that light can be extracted from the center of the window material 1, but it is not necessarily required to be formed up to the outer peripheral edge of the window material 1. The bonding layer 2 may be formed in the center of the window material 1 at a position that ensures a suitable range for extracting light, with a shape and area sufficient for airtight sealing.
[0047] The lid for optical element package of the present invention is, for example, formed by applying the sealing adhesive material of the present invention to a portion of the window material 1 that contacts the housing member 3 to form the adhesive layer 2. In this case, when the sealing adhesive material forming the adhesive layer 2 is to be in a semi-cured state (B-Stage), the adhesive layer 2 can be brought to a semi-cured state (B-Stage) by heating at 100 to 180°C for 5 to 60 minutes.
[0048] The window material 1 is not particularly specified as long as it is a transparent body that can transmit light. However, although the wavelength of the light emitting element 4 arranged in the housing member 3 is not particularly specified, in the case of a UV-LED that encapsulates an element that emits UV light, the window material 1 is preferably synthetic quartz that transmits short wavelengths with high transmittance. Since synthetic quartz exhibits high transmittance in a wide wavelength range, it is also applicable to light emitting elements in the visible light range, near infrared range, infrared range, etc.
[0049] By using such an optical element package lid having a bonding layer 2 made of the sealing bonding material of the present invention formed thereon, it is possible to form an optical element package, for example as shown in Fig. 1(C), which includes an optical element 4 and a housing member 5 housing the optical element 4 therein, in which a window material 1 and the housing member 3 are bonded together by the sealing bonding material of the present invention applied to the optical element package lid, and the optical element 5 is hermetically sealed inside the housing member 3. Note that reference numeral 5 in Fig. 1(C) is a reflector.
[0050] The window material 1 and the housing member 3 can be bonded, for example, as follows. First, the housing member 3 housing the optical element 4 is brought into contact with the bonding layer 2, and the bonding position is determined. The lid for the optical element package and the housing member 3 are then heat-treated to bond the two together. From the viewpoint of the heat resistance of the optical element sealed in the optical element package, the temperature of this heat treatment (curing temperature) is preferably 150° C. or higher, more preferably 170° C. or higher, and preferably 250° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower, and the time of the heat treatment is preferably 10 seconds to 60 minutes. At this time, it is preferable to simultaneously apply pressure, and the atmosphere in this treatment may be an air atmosphere, an inert gas atmosphere, a nitrogen gas atmosphere, or the like. In addition, when the sealing bonding material forming the bonding layer 2 is in a semi-cured state (B-Stage) as described above, the bonding layer 2 is crushed by heating, and the silver nanoparticles contained in the sealing bonding material are tightly bonded, making it possible to construct a more airtight seal.
[0051] In addition, in the lid for optical element package of the present invention, although not particularly limited, a thermal annealing step is preferably adopted in which the window material 1 and the housing member 3 housing the optical element 4 therein are bonded and integrated by the above-mentioned bonding layer 2, and then a heat treatment is further performed. This thermal annealing step makes the bonds between the silver nanoparticles in the bonding layer 2 formed by the sealing bonding material of the present invention, and between the silver nanoparticles and the plating powder, stronger, and the bonding strength can be increased. The temperature of the thermal annealing is preferably a temperature 20°C higher than the curing temperature (the temperature of the above-mentioned heat treatment), and more preferably a temperature 100°C higher than the curing temperature or lower [(curing temperature + 100°C) or lower]. Note that there is no particular upper limit on the temperature of the thermal annealing, but from the viewpoint of the heat resistance of the optical element 4 sealed in the optical element package, 250°C or lower is preferable. The time of the thermal annealing is preferably 10 to 180 minutes from the viewpoint of heat accumulation in the optical element 4 and productivity. EXAMPLES
[0052] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0053] [Example 1] The silver nanoparticles, which are made by coating the surface of silver core particles with an average primary particle diameter of 61 nm with undecanoic acid, are used at 23% by mass. The median diameter D 50 The solder powder was 65% by mass of Sn42-Bi58 solder (ST-5, Mitsui Mining & Smelting Co., Ltd.) with a diameter of 5.7 μm (by volume), 10% by mass of Tersolv THA-70 (Terpene Chemical Co., Ltd.) as a solvent, and the median diameter D 50 2% by mass of metallic selenium having a diameter of 8.3 μm (by volume) was mixed to obtain a sealing bonding material. The average primary particle size of the silver core particles was calculated as the arithmetic mean value of 20 random silver core particles observed with a scanning electron microscope (SEM). The same applies to the following examples.
[0054] [Example 2] The silver nanoparticles, which have an average primary particle diameter of 61 nm and are surface-coated with undecanoic acid, are used at 24% by mass. The median diameter D50 A sealing bonding material was obtained by mixing 65 mass% of Sn42-Bi58 solder powder (ST-5, Mitsui Mining & Smelting Co., Ltd.) with a diameter of 5.7 μm (by volume), 10 mass% of Tersolv THA-70 (Nippon Terpene Chemical Co., Ltd.) as a solvent, and 1 mass% of oleoyl sarcosine.
[0055] [Example 3] The silver nanoparticles, which have an average primary particle diameter of 58 nm and whose surfaces are coated with octanoic acid, are 21% by mass, and the median diameter D 50 The solder powder (ST-3, Mitsui Mining & Smelting Co., Ltd.) with a diameter of 3.4 μm (by volume) was used as 64 mass%, decanol was used as a solvent as 12 mass%, and the median diameter D 50 3 mass % of metallic selenium having a particle size of 8.3 μm (by volume) was mixed in to obtain a sealing bonding material.
[0056] [Example 4] The silver nanoparticles, which are made by coating the surface of silver core particles with an average primary particle diameter of 58 nm with undecanoic acid, are 26% by mass, and the median diameter D 50 A sealing bonding material was obtained by mixing 60 mass% of Sn88.0-In8.0-Ag3.5-Bi0.5 solder powder (ST-5, Mitsui Mining & Smelting Co., Ltd.) with a diameter of 5.8 μm (by volume), 12 mass% of a 1:1 mixed solvent of hexanol:decanol, and 2 mass% of Irganox 1010 (BASF Ltd.).
[0057] [Comparative Example 1] The silver nanoparticles, which have an average primary particle diameter of 61 nm and are surface-coated with undecanoic acid, are used at 24% by mass. The median diameter D 50 A sealing bonding material was obtained by mixing 65 mass% of Sn42-Bi58 solder powder (ST-5, Mitsui Mining & Smelting Co., Ltd.) having a diameter of 5.7 μm (by volume) and 11 mass% of Tersolv THA-70 (Nihon Terpene Kagaku Co., Ltd.) as a solvent.
[0058] <Verification of the effect of preventing and removing oxide film> For each of the obtained sealing adhesive materials, TG-DTA measurement was performed at a temperature increase rate of 5°C / min under atmospheric conditions. The measurement results for the sealing compositions of Examples 1 to 4 and Comparative Example 1 are shown in Figures 2 to 6. When the sealing adhesive material of Comparative Example 1 (Figure 6), which does not contain an antioxidant or a remover, is used as a control, it can be seen that when metallic selenium, an antioxidant or a remover is added (sealing adhesive materials of Examples 1 to 4, Figures 2 to 5), a change occurs in the TG-DTA curve.
[0059] 7 shows TG curves with the weight change on the vertical axis and the temperature on the horizontal axis for the sealing bonding materials of Examples 1 and 2 and Comparative Example 1. As shown in Fig. 7, the compositions of Examples 1 and 2 to which metallic selenium or an oxide film remover was added had less weight change compared to Comparative Example 1, indicating that oxidation of the metal substance used in the sealing bonding material of the present invention is effectively prevented.
[0060] <Lid for optical element packages> The sealing adhesive prepared in Examples 1 to 4 and Comparative Example 1 was applied by screen printing to one side of a synthetic quartz glass substrate in a 3.4 mm square window frame shape with a line width of 250 μm and a thickness of 30 μm to form an adhesive layer. Next, the synthetic quartz glass substrate on which the adhesive layer was formed was heated at 130° C. for 20 minutes to bring the adhesive layer into a semi-cured state (B-Stage). Then, the synthetic quartz glass substrate was diced along the outer periphery of the adhesive layer in the 3.4 mm square window frame shape to obtain a lid for optical element packages (synthetic quartz glass lid) having a synthetic quartz glass window material 1 and an adhesive layer 2, as in FIGS. 1(A) and (B).
[0061] <Evaluation of bonding layer during bonding> As in FIG. 1(C), an SMD package carrier made of aluminum nitride having a cavity structure as a storage section and gold-plated on the bonding surface was used as the storage member 3, and a UVC-LED emitting light of 285 nm or a photodiode as a light receiving element was stored as the optical element 4 in the cavity structure portion. 4The synthetic quartz glass lid having the bonding layer 2 formed thereon made of the sealing bonding material of Comparative Example 1 and Comparative Example 2 was placed on the package, and heated and pressed for 3 minutes at 150°C and 200g / package to bond the window material 1 and the housing member 2. Thereafter, thermal annealing was performed for 60 minutes in an electric furnace at 250°C to obtain an optical element package. The bonding layer of the obtained optical element package was evaluated by the following test. Note that, for this test, 50 test samples were prepared for evaluation.
[0062] [Red Check] The optical element package was immersed in Microcheck Penetrant JIP143 (manufactured by Ichinen Chemicals Co., Ltd.) for 24 hours, then washed with acetone and observed under a microscope. This red check was performed before and after the evaluation of resistance to ultraviolet light, which will be described later. Packages that showed no penetration of the liquid into the interior were deemed to have passed.
[0063] [Gross leak test] A gross leak test was conducted using a highly penetrating fluorine-based solvent in accordance with the US military standard MIL-STD-883 Method 1014. The optical element package was immersed in fluorine-based solvent FC-43 (Sumitomo 3M Co., Ltd.) heated to 120°C for two minutes, and the presence or absence of infiltration of the solvent into the optical element package was observed under a microscope. Packages that did not show any infiltration of the liquid into the package were deemed to have passed the test.
[0064] [Fine leak test] A fine leak test using helium was carried out in accordance with the US military standard MIL-STD-883 Method 1014. First, the optical element package was left in a vacuum for one hour, then left in a 0.3MPa helium gas atmosphere for six hours, after which the helium leak rate was measured using a helium leak tester. However, because synthetic quartz glass itself has the property of absorbing helium, the pass threshold was relaxed from the usual level to 5 x 10 -8 Those with atm cc / sec or less were considered to have passed.
[0065] [UV resistance evaluation] When the optical element was a UVC-LED, the UVC-LED in the optical element package was turned on for 5000 hours, after which the bonding state was observed and red check and gross leak tests were performed.On the other hand, when the optical element was a light receiving photodiode, ultraviolet light was irradiated from a UVC-LED emitting 285 nm light from above the window material of the optical element package for 5000 hours, after which the bonding state was observed and red check and gross leak tests were performed.
[0066] [Evaluation Results] The pass rate of the samples prepared for each example is shown below. [Table 1]
[0067] In addition, the sealing bonding materials of Example 2 and Comparative Example 1 were heated in the atmosphere at 150° C. for 3 minutes without load, and the cross sections of the formed films were observed. SEM photographs of the cross sections of the films are shown in FIGS. 8 and 9.
[0068] As shown in Figures 8 and 9, the sample film (Figure 8) formed with the sealing bonding material of Example 1 shows that the sealing bonding material is sufficiently dissolved to form a mixed and dense film. On the other hand, the sample film formed with the sealing bonding material of Comparative Example 1 shows that the metal components constituting the sealing bonding material form an oxide film, so that the metal particle shape remains and the film is not sufficiently dense. [Explanation of symbols]
[0069] 1 Window materials 2 Bonding layer 3. Storage material 4. Optical elements 5 Reflector
Claims
1. A sealing bonding material comprising solder powder, silver nanoparticles coated with a coating material, metallic selenium, and a solvent, the metallic selenium content being 0.5 to 5 mass %.
2. 2. The sealing adhesive according to claim 1, wherein the solder powder contains tin.
3. 3. The sealing bonding material according to claim 1, wherein the melting point of the solder powder is lower than the melting point of the metallic selenium.
4. 4. The sealing bonding material according to claim 2, wherein the solder powder contains tin and further contains bismuth.
5. 5. The sealing bonding material according to claim 4, wherein the solder powder further contains one or more elements selected from the group consisting of zinc, indium, and silver.
6. 6. The sealing bonding material according to claim 1, wherein the coating material is selected from the group consisting of aliphatic carboxylic acids, higher alcohols, and amines.
7. The sealing bonding material according to any one of claims 1 to 6, characterized in that the average primary particle diameter of the silver core portion of the silver nanoparticles is 20 to 90 nm, as measured by the following method. Measurement method: The average primary particle size was calculated as the arithmetic mean value of 20 randomly selected silver core particles observed with a scanning electron microscope (SEM).
8. The sealing bonding material according to any one of claims 1 to 7, characterized in that the solvent contains one or more compounds selected from the group consisting of terpenes, monoterpene alcohols, alkyl alcohols, and naphthenic hydrocarbons.
9. The metallic selenium is measured by a dynamic light scattering method. 50 The sealing bonding material according to any one of claims 1 to 8, characterized in that it contains metallic selenium having a size (volume basis) of 5 to 20 µm.
10. 10. The sealing bonding material according to claim 1, further comprising at least one oxide film remover selected from the group consisting of aliphatic carboxylic acids and polycarboxylic acids.
11. A sealing bonding material according to any one of claims 1 to 10, which contains one or more types of oxidation inhibitors selected from the group consisting of hindered phenols, hindered amines, hydroquinones, and phenothiazines.
12. A lid for an optical element package comprising a window material provided in front of a housing member in which an optical element is housed, in the direction of light emission of the optical element, and a metal-based bonding layer formed at a portion where the window material contacts the housing member, wherein a sealing bonding material described in any one of claims 1 to 11 is applied in a frame shape to the window material to form the metal-based bonding layer.
13. A lid for an optical element package as described in claim 12, characterized in that the window material is synthetic quartz glass.
14. A lid for an optical element package as described in claim 12 or 13, characterized in that the metal-based bonding layer formed from the sealing bonding material described in any one of claims 1 to 11 is in a semi-cured state (B-Stage).
Citation Information
Patent Citations
Sn-Zn lead-free solder containing Nd, Ga and Se
CN102848097A
Method for manufacturing optical disk
JP1985047254A
Solder paste
JP1985234793A
Cream solder
JP1989309795A
Cream solder and method for supplying solder
JP1996252687A